The Effects of Good Breeding Practices on Brucellosis Incidence in Kangal Akkaraman Sheep Flocks - Yusuf Ziya Oğrak; Nevin Tuzcu; Besim Ercan Ocak (Turkish Journal of Agriculture: Food Science and Technology)
The aim of the present study was to compare the incidence of brucellosis in groups of Kangal Akkaraman sheep flocks raised in farm conditions in Sivas province. The first and second groups of the sheep flocks were part of the 8 sub-projects which belong to The Project entitled “Nationwide Genetic Improvement of Small Ruminants in Farm Condition” continued for 7 and 1-3 years, respectively. The third group of the sheep flocks was not part of this nationwide project. The study material consisted of 1491 units of blood serum (n=278, 1166 and 47 for the first, second and third groups, respectively). Brucella antibodies were looked for in blood serum using tube and slide agglutination tests. The incidences of brucellosis were 4% and 7.5% in flocks which were part of the nationwide project continued for 7 and 3 years, respectively and 25.5% for the flocks not part of the nationwide project. The differences between groups were found statistically significant. Even though there was no brucella vaccination programs in the flocks of the nationwide project, practices such as regular controls of the flocks by veterinary technicians, drug/vaccination applications for parasites and some other diseases, removal of rams positive for brucella before breeding season significantly reduced the incidence of brucella. As a result, promoting good breeding practices along with the brucella vaccination program applied by the related Ministry can be very beneficial for the eradication of brucella disease that is a big problem for the country.